Oral activity of the antimalarial endoperoxide 6-(1,2,6,7-tetraoxaspiro[7.11]nonadec-4-yl)hexan-1-ol (N-251) against Leishmania donovani complex. - Kofi Dadzie Kwofie; Kai Sato; Chizu Sanjoba; Akina Hino; Rieko Shimogawara; Michael Amoa-Bosompem; Irene Ayi; Daniel A Boakye; Abraham K Anang; Kyung-Soo Chang; Mitsuko Ohashi; Hye-Sook Kim; et al. (Public Library of Science (PLoS), 2019)
Visceral leishmaniasis (VL) is a major problem worldwide and causes significant morbidity and mortality. Existing drugs against VL have limitations, including their invasive means of administration long duration of treatment regimens. There are also concerns regarding increasing treatment relapses as well as the identification of resistant clinical strains with the use of miltefosine, the sole oral drug for VL. There is, therefore, an urgent need for new alternative oral drugs for VL. In the present study, we show the leishmanicidal effect of a novel, oral antimalarial endoperoxide N-251. In our In vitro studies, N-251 selectively and specifically killed Leishmania donovani D10 amastigotes with no accompanying toxicity toward the host cells. In addition, N-251 exhibited comparable activities against promastigotes of L. donovani D10, as well as other L. donovani complex parasites, suggesting a wide spectrum of activity. Furthermore, even after a progressive infection was established in mice, N-251 significantly eliminated amastigotes when administered orally. Finally, N-251 suppressed granuloma formation in mice liver through parasite death. These findings indicate the therapeutic effect of N-251 as an oral drug, hence suggest N-251 to be a promising lead compound for the development of a new oral chemotherapy against VL.